Intestinal parasitic infections among children in central Albania - Sejdini, A.; Mahmud, R.; Lim, Y. A. L.; Mahdy, M.; Sejdini, F.; Gjoni, V.; Xhaferraj, K.; Kasmi, G. (Taylor & Francis, 2011)
Although intestinal parasitic infections (IPI) among children remain a global issue, the current information on such infections in Albanian children is very limited. A cross-sectional study of the IPI in 321 children living in the Albanian counties of Tirana (152) and Elbasan (169) was therefore conducted in 2008, with a pre-tested standard questionnaire employed to gather the relevant personal and clinical data. Using formalin-ether concentration and permanent stains, stool samples were examined microscopically for the ova, cysts and oocysts of any parasites. The overall prevalence of IPI was 19 (61 of 321), with protozoan infections (11.5) apparently more common than infections with soil-transmitted helminths (STH; 8.1). Giardia duodenalis was the parasite most frequently detected (10.9), followed by hookworm (5.6), Ascaris lumbricoides (1.9), Trichuris trichiura (0.6), Cryptosporidium (0.3) and Entamoeba histolytica/dispar (0.3). The results of a univariate analysis indicated that the children from Tirana county were significantly more likely to be found infected with STH compared with the children from Elbasan county (12.5 v. 4.1; P=0.006). Children sampled in the community were also more likely to be found STH-positive than the children sampled as they attended hospitals and health clinics (10.5 v. 6.0) but this difference did not reach statistical significance. The children found STH-positive were five times more likely to be suffering from diarrhoea than the other children checked in clinical settings (P=0.004) and were also more likely to be suffering from abdominal pain (P=0.054) and/or diminished appetite (P=0.016).